1873 Nev. Comp. Laws 563 - (:unkn) unknown (My University, 1873)
Offenses Against The Persons of Individuals, §§ 35-36: Prohibited dueling and killing a person with a rifle, shotgun, pistol, Bowie knife, dirk, small sword, backsword, or other dangerous weapon.
Keywords: DUELING